The quotient rule of exponents states that when dividing two exponential expressions with the same base, you subtract the exponents.
For example, if we have the expression (x^3)/(x^2), we can apply the quotient rule of exponents by subtracting the exponents of x:
x^3 / x^2 = x^(3-2) = x^1 = x
Let's practice using the quotient rule of exponents with some more examples:
1) (a^5)/(a^3)
To divide the expression, we subtract the exponents:
(a^5)/(a^3) = a^(5-3) = a^2
2) (z^8)/(z^4)
Again, subtract the exponents to divide:
(z^8)/(z^4) = z^(8-4) = z^4
3) (2^6)/(2^3)
Apply the quotient rule by subtracting the exponents:
(2^6)/(2^3) = 2^(6-3) = 2^3 = 8
4) (m^2)/(m^4)
When the exponent in the denominator is greater than the exponent in the numerator, the result will be a fraction with a negative exponent:
(m^2)/(m^4) = 1/(m^(4-2)) = 1/m^2
5) (10^5)/(10^5)
Since the exponents are the same, the result will be 1:
(10^5)/(10^5) = 1
These are some examples of how to use the quotient rule of exponents in practice. Remember to subtract the exponents when dividing exponential expressions with the same base.
Quotient rule of exponents practice
1 answer